2020
DOI: 10.1088/1674-4926/41/3/032102
|View full text |Cite
|
Sign up to set email alerts
|

Small-signal modeling and parameter extraction method for a multigate GaAs pHEMT switch

Abstract: This paper presents an accurate small-signal model for multi-gate GaAs pHEMTs in switching-mode. The extraction method for the proposed model is developed. A 2-gate switch structure is fabricated on a commercial 0.5 μm AlGaAs/GaAs pHEMT technology to verify the proposed model. Excellent agreement has been obtained between the measured and simulated results over a wide frequency range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Using the presented parameter extraction method, the model simulated results with measured data show excellent agreement with the measurements up to 10.1 GHz in Figure 6. To better illustrate the effectiveness of the extracted small signal model parameter extraction method and the fitting accuracy of the new model under Bias 1, Bias 2 and Bias 3, the relative error formula 33 is introduced to evaluate it. e=SsimuiSmeasinSmeasi2n1emi=1,2n, where e is the relative error; S simu ( i ) is the i th simulation data; S meas ( i ) is the i th measurement data; and n represent number of data point in the frequency range of 0.6–10.1 GHz. Table 2 shows the results of the evaluation of the relative errors of the S ‐parameters obtained from the measurements and simulations of the model.…”
Section: Model Verificationmentioning
confidence: 99%
“…Using the presented parameter extraction method, the model simulated results with measured data show excellent agreement with the measurements up to 10.1 GHz in Figure 6. To better illustrate the effectiveness of the extracted small signal model parameter extraction method and the fitting accuracy of the new model under Bias 1, Bias 2 and Bias 3, the relative error formula 33 is introduced to evaluate it. e=SsimuiSmeasinSmeasi2n1emi=1,2n, where e is the relative error; S simu ( i ) is the i th simulation data; S meas ( i ) is the i th measurement data; and n represent number of data point in the frequency range of 0.6–10.1 GHz. Table 2 shows the results of the evaluation of the relative errors of the S ‐parameters obtained from the measurements and simulations of the model.…”
Section: Model Verificationmentioning
confidence: 99%
“…[15][16][17][18] However, switch-HEMT modeling remains challenging as only a few works studied its pitfalls. [19][20][21][22][23][24][25][26] In practice, switch-HEMTs usually operate in the common-gate (CG) configuration. A large-valued resistor is connected to the gate of the switch-HEMT to prevent RF leakage to the bias circuitry.…”
Section: Introductionmentioning
confidence: 99%
“…Several papers addressed the switch-HEMT modeling challenge by neglecting or incorporating the large gate resistor into the intrinsic equivalent circuit equations. 19,20 In the work by Giofre et al, 21 an electromagnetic (EM) based approach similar to commonsource (CS) modeling and cascode modeling, initially proposed by Resca et al, [27][28][29][30] was suggested. Several EMsimulations were applied to derive the small-signal behavior of the CG switch-HEMT using the measured S-parameters of the CS device as the model core.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations